2014
DOI: 10.3390/min4030565
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Rich, Iron Oxide Microtubular Sheath Produced by an Iron-Oxidizing Bacterium, Leptothrix sp. Strain OUMS1, in Culture

Abstract: This study aimed to manipulate the texture and elemental composition of the novel sheaths produced by the iron-oxidizing bacterium Leptothrix in culture by altering components of the medium. When previously isolated strain OUMS1 was cultured in media (pH 7.0 throughout incubation) containing various levels of Si on a rotary shaker at 20 °C and 70 rpm for 14 days, the strain was able to reproduce in media with up to 300 ppm Si, and the hollow microtubular architecture of the sheath was maintained even at 300 pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…Similar to the finding by Eggleton et al [22], a very broad peak at 30-40° and around 61° (black triangle in line A of Figure 4), plausibly was derived from two-line ferrihydrite (2Fh) [7], was observed for sheaths formed in the Fe plate medium. The sheaths that formed in the 0.14 g/L Fe powder medium showed a broad peak between 2θ = 15° and 31° (highest at 2θ = 20°), which was probably derived from C-containing constituents of bacterial and/or medium origin [23], and no remarkable peaks for the presence of Fe oxides were detected (line B of Figure 4).…”
Section: Crystallinity Of Sheaths Detected By Xrdsupporting
confidence: 76%
See 3 more Smart Citations
“…Similar to the finding by Eggleton et al [22], a very broad peak at 30-40° and around 61° (black triangle in line A of Figure 4), plausibly was derived from two-line ferrihydrite (2Fh) [7], was observed for sheaths formed in the Fe plate medium. The sheaths that formed in the 0.14 g/L Fe powder medium showed a broad peak between 2θ = 15° and 31° (highest at 2θ = 20°), which was probably derived from C-containing constituents of bacterial and/or medium origin [23], and no remarkable peaks for the presence of Fe oxides were detected (line B of Figure 4).…”
Section: Crystallinity Of Sheaths Detected By Xrdsupporting
confidence: 76%
“…As illustrated in Figure 3E,F, EDX analysis revealed a homogeneous distribution of Fe in a sheath that was harvested from the Fe powder medium. This distribution pattern was very similar to that in sheaths harvested from a two week culture of OUMS1 in the Fe plate medium as reported earlier [7,16]. The average atomic percentages of Fe in 10 spots of sheaths harvested after two weeks were 66.9 ± 9.9%, 82.4 ± 3.8%, and 88.9 ± 6.1% in 0.14, 1.4, and 14 g/L Fe powder medium, respectively, showing that Fe encrustation increased with increasing amount of Fe source in the medium.…”
Section: Morphology and Fe Distribution Of Sheathssupporting
confidence: 61%
See 2 more Smart Citations
“…Our previous study further indicated that the chemical character and crystallinity of the sheath matrix can be modified depending on the culture conditions for the strains, especially on the components of the medium [30]. These findings encouraged us to elucidate the encrustation mechanism of sheaths in culture in more detail so that we can rationally manipulate the matrix and elemental composition of Leptothrix sheaths to further increase the usefulness of the material and to create novel functional materials.…”
Section: Introductionmentioning
confidence: 99%